Disease spectrum of patients with hospital-acquired multidrug-resistant organism infections in the intensive care unit: a retrospective study - Wang, Xiaowu; Liu, Yan; Ding, Yunyun; Li, Mei; Gao, Yong; Li, Tuantuan (Frontiers in Microbiology, 2025)
ObjectiveTo understand the infection status and disease spectrum distribution of patients with hospital-acquired Multidrug-resistant Organism (MDRO) Infections in an intensive care unit (ICU) before, during, and after the Coronavirus Disease 2019 (COVID-19) Pandemic, and provide a basis for the prevention and control of hospital-acquired MDRO infections.MethodsData from the Second People’s Hospital of Fuyang City’s ICU was analyzed from three periods: pre-COVID-19 (January 1, 2018-December 8, 2019), during COVID-19 (December 9, 2019-December 7, 2022), and post-COVID-19 (December 8, 2022-December 31, 2023). The study compares the disease spectrum of MDRO infections patients across these periods.ResultsThe incidence density of hospital-acquired MDRO infections showed significant variation over the six-year period, with the highest density in the post-COVID-19 period (43.98 per 1,000 ICU days) and the lowest during the COVID-19 period (21.96 per 1,000 ICU days). The mortality rate associated with MDRO infections was minimized during the COVID-19 pandemic (2.70 per 1,000 ICU days) and rebounded in the post-COVID-19 period (10.66 per 1,000 ICU days). The infection rate of Acinetobacter baumannii (A. baumannii) increased in the post-COVID-19 group compared to the pre-COVID-19 and during-COVID-19 groups (χ2 = 8.82, p = 0.012). Respiratory diseases consistently ranked first pre-, during, and post-COVID-19 pandemic. The proportion of nervous system diseases in the post-COVID-19 group was lower than in the pre-COVID-19 and during COVID-19 groups (p < 0.05), while the proportions of respiratory diseases and acute abdomen were higher than in the pre-COVID-19 and during-COVID-19 groups (p < 0.05). Among ICU MDRO patient death cases, the proportion of respiratory diseases in the post-COVID-19 group was higher than in the pre-COVID-19 and during-COVID-19 groups (p < 0.05).ConclusionOur data show the mortality rate of hospital-acquired MDRO infections decreased during COVID-19 and increased after restrictions eased. The disease spectrum of MDRO-infected patients is complex and diverse. Standardized, accurate treatment and focused management of respiratory diseases are essential, along with strengthened infection prevention measures.